Infinite-dimensional analysis related to generalized translation operators - Berezansky, Yu. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We give an extensive generalization of the white-noise analysis (in the Gaussian and non-Gaussian case) in which the role of translation operators is played by a fixed family of generalized translation operators.